PELATIHAN PEMANFAATAN TEKNOLOGI KOMPUTER DALAM PENGOLAHAN DATA PASIEN PADA UPT. PUSKESMAS PORSEA - Risnawati Risnawati; Masitah Handayani; Syartika Anggraini (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2020)
Abstract: Community Service activities are in the form of training in the use of computer technology for health workers, especially the patient registration section in the UPT Porsea Health Center environment, aimed at providing knowledge and skills, which are expected to produce changes in knowledge and skills from teachers and students so that the learning and teaching process can run smoothly and easily. The target audience in this Community Service activity is all health workers on duty in the patient registration section. Training activities on the use of computer technology in the world of health are presented with lecture methods, demonstrations and question and answer. Benefits obtained from this activity include increasing knowledge of staff health to be more professional in processing the data of patients who are treated at the UPT Porsea Health Center in order to manage patient data effectively and efficiently in science and technology mastery, so that it can simplify the process of calculating the number of patients treated computerically with the help of Microsoft Excel. Keywords: Utilization of Computer Technology, Microsoft Excel, Patient Data Processing  Abstrak: Kegiatan Pengabdian kepada Masyarakat berupa pelatihan pemanfaatan teknologi komputer bagi tenaga kesehatan khususnya bagian pendaftaran pasien di lingkungan UPT Puskesmas Porsea ini bertujuan untuk memberikan pengetahuan dan keterampilan, yang diharapkan dapat menghasilkan perubahan pengetahuan, keterampilan dan sikap dari guru maupun siswa sehingga proses belajar dan mengajar dapat berjalan dengan lancar dan mudah.Khalayak sasaran dalam kegiatan Pengabdian kepada Masyarakat ini adalah seluruh tenaga kesehatan yang bertugas di bagian pendaftaran pasien. Kegiatan pelatihan pemanfaatan teknologi komputer dalam dunia kesehatan ini disajikan dengan metode ceramah, demonstrasi dan tanya jawab. Manfaat yang diperoleh dari kegiatan ini antara lain dapat meningkatkan pengetahuan tenaga kesehatan agar lebih profesional dalam mengolah data pasien yang berobat di UPT Puskesmas Porsea agar dapat mengelola data pasien secara efektif dan efisien dalam penguasan IPTEKS, sehingga dapat mempermudah proses perhitungan jumlah pasien yang berobat secara komputerisasi dengan bantuan Microsoft Excel. Kata Kunci : Pemanfaatan Teknologi Komputer, Microsoft Excel, Pengolahan Data Pasien